A Study of Mitochondrial Dynamics and Glycosylation Events in PC12 Cells and Neurons - O HARA, DARREN (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2017)
Summary Mitochondrial dysfunction is recognised as a hallmark of many neurodegenerative diseases. Altered electron transport chain (ETC) complex activities, mitochondrial fusion/fission dynamics, mitochondrial motility kinetics and quality control of mitochondrial biogenesis have been implicated in the pathogenesis of Parkinson?s Disease (PD) and Alzheimer?s Disease (AD). However, further elucidation of the mechanisms that underlie dysfunctions in mitochondrial dynamics is required. This study characterizes the effect of electron transport chain (ETC) inhibition on mitochondrial dynamics in differentiated PC12 cells and primary cortical neurons. Inhibition of any of the ETC complexes, ATP synthase or dissipation of the mitochondrial membrane potential was sufficient to completely abolish mitochondrial fusion in differentiated PC12 cells. This effect is dependent on a post-translational modification that cleaves OPA1, the protein responsible for inner mitochondrial membrane fusion, to a shorter form, thus inhibiting fusion. It was also found that complex I inhibition has a threshold effect on mitochondrial fusion in primary cortical neurons as 55% inhibition of complex I completely inhibits mitochondrial fusion while 53% inhibition has no significant effect. This effect also correlated with a mitochondrial membrane potential dependent cleavage of Opa1. Mutations in, and abnormal accumulation of, the presynaptic protein a-synuclein are highly correlated with the pathogenesis of PD. Accumulations of this protein have been shown to inhibit complex I. Overexpression of both wild-type and mutant forms of a-synculein were found to decrease mitochondrial fusion in differentiated PC12 cells, suggesting that a-synculein dependent changes in fusion/fission dynamics may be a complicating factor in PD. Altered substrate utilization and O-GlcNAcylation have also been linked to the progression of some neurodegenerative diseases. In this study, inhibition of fatty acid oxidation and pyruvate transport into the mitochondrion decreased mitochondrial fusion in differentiated PC12 cells. O-GlcNAcylation is a post- translational modification that attaches O-GlcNAc moieties to cytoplasmic, nuclear and mitochondrial proteins. Investigation into acute increases in O- GlcNAcylation, induced by inhibition or knockdown of O-GlcNAcase, revealed decreases in mitochondrial fusion, elongated mitochondrial morphology, increased respiration rates and increased complex I activity. A decrease in the level of O-GlcNAcylation, induced by inhibition or knockdown of O-GlcNAc transferase, resulted in increased mitochondrial fusion, decreased mitochondrial membrane potential, fragmented mitochondrial morphology and decreased respiration rates in differentiated PC12 cells. Knockdown of O-GlcNAc transferase also resulted in increased ROS production. The results presented in this thesis point to altered complex I activity having an important role in mitochondrial dysfunction and subsequently, mitochondrial dynamics in the brain. Identification of compounds which can regulate complex I activity, may be able to restore balance to mitochondrial dynamics and halt or slow the progression of neurodegenerative diseases. Finally, this study demonstrated it is possible to visualize the cell surface glycome of primary cortical neurons by metabolic labelling. Three modified azido sugars were incorporated into the cell surface glycome and labelled using click chemistry. Super resolution microscopy identified intriguing heavily sialylated structures on the cell surface of neuronal projections. In addition to this, use of inhibitors of various glycosyltransferases allowed for some elucidation of the make-up of the neuronal cell surface glycome which was found to be predominantly N-glycans. These findings may help to identify glycans important for neuronal differentiation and synaptic transmission.
APPROVED
Keywords: Mitochondria; Mitochondrial Dynamics; Neurodegeneration; Glycosylation; O-GlcNAc